PENGGUNAAN ASAM HUMIK DALAM KULTUR TRAPPING CENDAWAN MIKORIZA ARBUSKULA DARI EKOSISTEM DENGAN SALINITAS TINGGI - Delvian Delvian (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
It has been reported that humic acid can increase plant growth and benefecial soil microbe population.   A glasshouse experiment was conducted to study the effect of humic acid on growth of host plant and sporulation of arbuscular mycorrhizal fungi under salt stress in trap pot culture. Trap cultures were maintenance at various salinity levels as according to field salinity.  Half of the pots received 2.5% humic acid and control treatment received no humic acid. Result of research indicate that humic acid  can increase growth of host plant and mycorrhizae sporulation at all salinity levels. Acaulospora  is highest   its spore production   followed by of Glomus and Gigaspora .